Entrepreneur muslimah: kekuatan internal menghadapi globalisasi - nabila, dinda nisa u (Maliki Interdisciplinary Journal, 2026)
Muslim women entrepreneurs in the era of globalization, is seen not only as a driver of the family economy, but also as an important means to meet the psychological needs and self-actualization of a Muslim woman. Muslimahpreneur specifically integrates the spiritual and ethical aspects of Islamic morality in every business decision, while maintaining the boundaries of dignity and social harmony. But there are many challenges facing entrepreneurs, such as gender stereotypes, limited access to capital, and the pressure to balance intense family and business responsibilities. The key to success of Muslimahpreneur is to master entrepreneurial knowledge, entrepreneurial skills, entrepreneurial motivation, strong intentions, and self-efficacy to face risks. Spiritual values ​​are essential for achieving prosperity. Despite this freedom, Islam emphasizes the importance of maintaining ethical and dignified boundaries, and ensuring that business activities are conducted without compromising moral integrity and social harmony.